The centrosome-nucleus complex and microtubule organization in the Drosophila oocyte. - Januschke, J.; Gervais, L.; Gillet, L.; Keryer, G.; Bornens, M.; Guichet, A. (Development, 2006)
Molecular motors transport the axis-determining mRNAs oskar, bicoid and gurken along microtubules (MTs) in the Drosophila oocyte. However, it remains unclear how the underlying MT network is organized and how this transport takes place. We have identified a centriole-containing centrosome close to the oocyte nucleus. Remarkably, the centrosomal components, gamma-tubulin and Drosophila pericentrin-like protein also strongly accumulate at the periphery of this nucleus. MT polymerization after cold-induced disassembly in wild type and in gurken mutants suggests that in the oocyte the centrosome-nucleus complex is an active center of MT polymerization. We further report that the MT network comprises two perpendicular MT subsets that undergo dynamic rearrangements during oogenesis. This MT reorganization parallels the successive steps in localization of gurken and oskar mRNAs. We propose that in addition to a highly polarized microtubule scaffold specified by the cortex oocyte, the repositioning of the nucleus and its tightly associated centrosome could control MT reorganization and, hence, oocyte polarization.